2010
DOI: 10.1016/j.ydbio.2010.07.037
|View full text |Cite
|
Sign up to set email alerts
|

poky/chuk/ikk1 is required for differentiation of the zebrafish embryonic epidermis

Abstract: An epidermis surrounds all vertebrates, forming a water barrier between the external environment and the internal space of the organism. In the zebrafish, the embryonic epidermis consists of an outer enveloping layer (EVL) and an inner basal layer that have distinct embryonic origins. Differentiation of the EVL requires the maternal effect gene poky/ikk1 in EVL cells prior to establishment of the basal layer. This requirement is transient and maternal Ikk1 is sufficient to allow establishment of the EVL and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 63 publications
3
45
1
Order By: Relevance
“…Epiboly defects may be in part due to abnormal cytoskeletal structures, as we observed disruptions in the actin cytoskeleton in npc1 morphants. Unlike some zebrafi sh mutants and morphants that have epiboly delay, Npc1-morphant zebrafi sh did not show a reduction in EVL integrity ( 45,46 ) or any decline to the ability of the leading cells to undergo necessary shape changes during epiboly ( 47 ). The phenotype cannot be attributed to cell death during early developmental stages as we did not detect any increases in apoptosis in these morphant embryos.…”
Section: This Work Was Supported By a Ruth L Kirschtein Predoctoralcontrasting
confidence: 70%
See 1 more Smart Citation
“…Epiboly defects may be in part due to abnormal cytoskeletal structures, as we observed disruptions in the actin cytoskeleton in npc1 morphants. Unlike some zebrafi sh mutants and morphants that have epiboly delay, Npc1-morphant zebrafi sh did not show a reduction in EVL integrity ( 45,46 ) or any decline to the ability of the leading cells to undergo necessary shape changes during epiboly ( 47 ). The phenotype cannot be attributed to cell death during early developmental stages as we did not detect any increases in apoptosis in these morphant embryos.…”
Section: This Work Was Supported By a Ruth L Kirschtein Predoctoralcontrasting
confidence: 70%
“…We constructed riboprobes from plasmids containing a selected region of ntl ( 53 ), fkd6 ( 54 ), papc ( 55 ), gsc ( 56 ), krt4 ( 57 ), krt18 ( 58 ), cldnE ( 59 ), krt8 ( 45,46,60,61 ), and sox32 ( 62 ) zebrafi sh genes. Embryos were visualized on a Leica MZ16F microscope equipped with a Leica DFC 490 digital camera.…”
Section: Whole Mount In Situ Hybridization and Embryo Stainingmentioning
confidence: 99%
“…It has been reported that defects in EVL differentiation can induce defects in epiboly (Fukazawa et al, 2010). In order to rule out the possibility that the defect in EVL morphology and the delay in epiboly were caused by a defect in EVL differentiation, we performed ISH for keratin4 (krt4) mRNA at the dome stage (supplementary material Fig.…”
Section: E-catenin Depletion Causes a Delay In Epibolymentioning
confidence: 99%
“…1) and acts similarly in oxygen exchange (McLeish et al, 2010;Schwerte, 2010). The basal layer consists of cells that express the epithelial stem cell marker p63 (Bakkers et al, 2002;Lee and Kimelman, 2002), whereas the periderm is an outer superficial layer of differentiated cytokeratin-positive cells (Gong et al, 2002;Wang et al, 2006) that are derived from the enveloping layer (Fukazawa et al, 2010) (Fig. 1A,B).…”
Section: Identification Of Gal4 Enhancer Lines Expressed In Distinctmentioning
confidence: 99%
“…Additionally, the epidermis of the developing zebrafish contains several specialized cell types that allow for the exchange of oxygen, ions and macromolecules, similar to mammalian bilayered epithelia (Hwang, 2009;Jevtov et al, 2014;Schwerte, 2010). Mammalian genes involved in epithelial morphogenesis, maintenance and disease conditions are conserved in zebrafish (de la Garza et al, 2013;Fukazawa et al, 2010;Lee and Kimelman, 2002;Li et al, 2011;Sabel et al, 2009;Sonawane et al, 2009). Further, gene function within the epidermis can be readily probed using mutations, morpholinos and chemical inhibitors.…”
Section: Introductionmentioning
confidence: 99%